2016
DOI: 10.1364/josab.33.000c10
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling coherent quantum feedback for Pyragas control

Abstract: We present a Heisenberg operator based formulation of coherent quantum feedback and Pyragas control. This model is easy to implement and allows for an efficient and fast calculation of the dynamics of feedback-driven observables as the number of contributing correlations grows in systems with a fixed number of excitations only linearly in time. Furthermore, our model unravels the quantum kinetics of entanglement growth in the system by explicitly calculating non-Markovian multi-time correlations, e.g., how the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…In the limit of high photon number, semiclassical approximations allow to derive manageable equations and establish the ties to the classical regime [20,21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the limit of high photon number, semiclassical approximations allow to derive manageable equations and establish the ties to the classical regime [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…To solve this problem methods have been proposed employing the Liouville space [26], Matrix product state (MPS) evolution [27], and the Heisenberg picture [21].…”
Section: Introductionmentioning
confidence: 99%
“…This clearly involves some intrinsically classical, stochastic signals even if the system to be controlled is fully quantum. In contrast, passive feedback [6] (not discussed here) is essentially the embedding of a (quantum) system into a larger (quantum) system such that effectively, some parts of the enlarged system control the original system, without the need of permanent, external observation [7][8][9][10][11][12][13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…[37][38][39][40][41][42][43][44][45][46] Various setups to control quantum few-level systems via timedelayed feedback have been studied theoretically and it has been shown that it is possible to control characteristic quantities such as the photon-photon correlation and the concurrence which functions as a measure of entanglement. [47][48][49][50][51][52][53][54][55][56][57][58][59] In these systems, in general, the control parameters that can be used to evoke the desired behavior are the delay time and the characteristic frequency which, depending on the considered setup, can be, for example, the frequency of an involved optical transition or the frequency of a cavity mode. These parameters influence the dynamics via the feedback amplitude x(t − ) and the phase = .…”
Section: Introductionmentioning
confidence: 99%